Detection of Adulterants in the Essential Oil by Curcuma aeruginosa Roxb. FTIR Spectroscopy and Multivariate Analysis - Bekti Nugraheni; Ratna Asmah Susidarti; Purwanto Purwanto; Abdul Rohman (Journal of Food and Pharmaceutical Sciences, 2026)
Authentication of Curcuma aeruginosa Roxb. essential oils (EOs-CA) is critical to prevent adulteration and to ensure the quality and safety of derived products. This study aimed to evaluate the effectiveness of Fourier Transform Infrared (FTIR) spectroscopy in combination with chemometric methods for the authentication of EOs-CA, particularly in the presence of adulterants such as Virgin Coconut Oil (VCO). VCO was selected as an adulterant model due to its spectral similarity with EOs-CA. Discriminant Analysis (DA) and multivariate calibration techniques—Partial Least Squares (PLS) and Principal Component Regression (PCR)—were employed for the classification and quantification of adulterated EOs-CA samples, including those mixed with Curcuma xanthorrhiza essential oil (EOs-CX). A total of 26 samples were prepared, comprising binary mixtures of EOs-CA/EOs-CX and ternary mixtures of EOs-CA/EOs-CX/VCO, with adulterant concentration levels ranging from 0% to 100%. FTIR spectral data were collected in the wavenumber range of 4000–650 cm⁻¹ using an Agilent Cary 630 FTIR-ATR spectrophotometer (USA). Chemometric analyses were conducted using DA, PLS, and PCR methods through TQ Analyst software version 9 (Thermo Fisher Scientific, Inc.). The DA method successfully classified authentic and adulterated samples with accuracy rates of 99.99% and 99.96% for the binary and ternary systems, respectively. Quantitative determination of EOs-CA in binary mixtures with EOs-CX was achieved using the second derivative of FTIR spectra in the 1770–728 cm⁻¹ region, yielding coefficients of determination (R²) of 0.9992 and 0.9994 for the calibration and validation models, respectively. The Root Mean Square Error of Calibration (RMSEC) and Prediction (RMSEP) were 1.19% and 1.16%, respectively. These findings demonstrate that FTIR spectroscopy combined with chemometric techniques provides a reliable and accurate method for detecting adulteration and authenticating EOs-CA against potential adulterants such as EOs-CX and VCO.